Dance Umbrella 2005 Mark Morris Dance Group - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Programme two reviewed. PALABRAS CLAVE: Mark Morris Dance Group, Mosaic and United.
Dentro del apartado "Dance Umbrella 2005".